Hepatoprotective effect of silymarin - Nancy Vargas-Mendoza Eduardo Madrigal-Santillán ngel Morales-González Jaime Esquivel-Soto Cesar Esquivel-Chirino Manuel García-Luna y González-Rubio Juan A Gayosso-de-Lucio José A Morales-González (World journal of hepatology, 2014)
The use of medicinal plants in treating illnesses has been reported since ancestral times.In the case of hepatic diseases,several species such as Silybum marianum,Phyllanthus niruri,and Panus giganteus(Berk.)have been shown to ameliorate hepatic lesions.Silymarin is a natural compound derived from the species Silybum marianum,which is commonly known as Milk thistle.This plant contains at least seven flavoligands and the flavonoid taxifolin.The hepatoprotective and antioxidant activity of silymarin is caused by its ability to inhibit the free radicals that are produced from the metabolism of toxic substances such as ethanol,acetaminophen,and carbon tetrachloride.The generation of free radicals is known to damage cellular membranes and cause lipoperoxidation.Silymarin enhances hepatic glutathione and may contribute to the antioxidant defense of the liver.It has also been shown that silymarin increases protein synthesis in hepatocytes by stimulating RNA polymerase I activity.A previous study on humans reported that silymarin treatment caused a slight increase in the survival of patients with cirrhotic alcoholism compared with untreated controls.